ORDOVICIAN TRILOBITES OF THE SUBFAMILY ASAPHINAE OF THE LADOGA GLINT - Ivantsov A.Yu. (My University, 2003)
Trilobites of the subfamily Asaphinae Burmeister (genus Asaphus s.l.) coming from natural out-crops of the Ordovician beds on the southern shore of Lake Ladoga are monographically studied and revised. Forty-one taxa of the generic and specific ranks, including seven new taxa, are described; they constitute more than three-quarters of this widely known group of European Ordovician trilobites. Some points of asaphine ecology and phylogeny are considered. Considerable attention is paid to the stratigraphy of the Early-Middle Ordovician deposits of the eastern part of the northern Estonia-Lithuania confacial belt or the gray limestone zone, which is the parental facies of many trilobite groups of the Baltic Paleobasin.
Keywords: trilobites; Asaphinae; Russia; Ladoga; Ordovician; Paleozoic::Ordovician; Палеозой::Ордовикская